Influence of preinfarction angina on the release kinetics of endothelial progenitor cells and cytokines during the week after infarction - Jiménez-Navarro, Manuel Francisco; Caballero-Borrego, Juan; Rodríguez-Losada, Noela; Cabrera-Bueno, Fernando; Marchal, Juan Antonio; Estebaranz, Javier; Muñoz-García, Antonio Jesús; Perán-Quesada, Macarena; Pérez-Martín, Margarita; Ramirez, Gemma; Hernández García, José María; Aránega, Antonia; et al. (Wiley Online Library, 2011)
Preinfarction angina, a possible form of ischaemic preconditioning, improves the prognosis inpatients who experience a major ischaemic event; though the associated pathophysiology is not yet fully under-stood. The aim of this study was to determine the possible involvement of endothelial progenitor cells (EPC), thevascular endothelial growth factor (VEGF) and the hepatocyte growth factor (HGF) in the development ofpreinfarction angina
Keywords: Infarto de miocardio; Endothelial progenitor cells; Cytokines